Numerical Study of Cavitation Effect on Hydrodynamic Characteristics of Hydrofoil - Nur Ikhsan, Aditya
This research aims to determine the effect of the cavitation on hydrodynamic characteristics of hydrofoil. Important parameters examinded in this research is the cavitation number. The value of the cavitation parameter is varieted so that it can obtain supercavitation, sheet cavitation, and non-cavitating conditions. Analysis of cavitation phenomenon is carried out with computational fluid dynamics (CFD) methods using ANSYS Fluent software based on a solution of RANS equations with multiphase mixture cavitation model and turbulent k-? RNG model. The results shown the increase in cavitation number resulting a reduction in volume of generated air bubbles. The location of the cavitation on the MH 115 cambered hydrofoil is closer to the leading edge, as the cavitation number value increased, while the symmetric hydrofoil NACA 16 series remains at the leading edge. The cavitation phenomenon provides an impact on the reduction of hydrodynamic efficiency. The value of hydrodynamic efficiency, CL / CD is used as a criterion to determine the type of hydrofoil for ROV by observing the effect of cavitation.